2021
DOI: 10.1111/ijn.12974
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of three pain relief methods for inserting a needle into the implanted venous access chemoport: A randomized controlled trial

Abstract: Aims Effective methods for relieving pain in inserting a needle for chemotherapy in cancer patients have been studied. This study examined the pain relief effects during needle insertion into the implanted venous access chemoport by comparing three methods. Methods This randomized controlled trial included 120 cancer patients who were randomly assigned. The experimental groups received applications of lidocaine cream (n = 30), cryotherapy (n = 30) and cutaneous stimulation therapy (n = 30); the control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In this parallel randomized controlled trial, the intervention group was subjected to lidocaine spray treatment, while the control group was a blank control, and the pain score was the primary outcome indicator. According to previous literature [ 10 ], the pain caused by non-coring needle puncture at the TIVAP was 3.91 ± 1.35 in the control group and 1.57 ± 0.68 in the lidocaine cream intervention group. Setting α=0.05 (bilateral) and β=0.10, the sample size in the intervention group and the control group was calculated as N1=N2=5 using the PASS11 software.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this parallel randomized controlled trial, the intervention group was subjected to lidocaine spray treatment, while the control group was a blank control, and the pain score was the primary outcome indicator. According to previous literature [ 10 ], the pain caused by non-coring needle puncture at the TIVAP was 3.91 ± 1.35 in the control group and 1.57 ± 0.68 in the lidocaine cream intervention group. Setting α=0.05 (bilateral) and β=0.10, the sample size in the intervention group and the control group was calculated as N1=N2=5 using the PASS11 software.…”
Section: Methodsmentioning
confidence: 92%
“…The infusion or maintenance period after port placement requires puncture with a non-coring needle, but patients often complain of significant pain during the puncture as the structure of the non-coring needle slows down its speed through the skin [ 8 ]. It is reported that the incidence of mild and moderate to severe pain caused by TIVAP needle insertion is 67.5% and 34.9%, respectively [ 9 ], and the pain score can reach 3.91 ± 1.35 [ 10 ]. The pain caused by needle puncture is related to the fear and suffering of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of pain management depends on the nurse's knowledge, attitude, and skill regarding painful interventions (Savcı et al, 2022). The American Society for Pain Management Nursing endorses pain control before and during painful procedures (Shin et al, 2022). Also, immunization guidelines suggest that site pain should be prevented, and therefore inexpensive interventions which are easy to implement need to be available (Redfern et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that the 2.5% lidocaine had no impact in reducing the discomfort brought on by hemodialysis needle insertion [27]. Additionally, a study comparing the efficiency of lidocaine cream and cryotherapy for putting a needle into the implanted venous access chemotherapy port revealed that lidocaine cream had the strongest effect, followed by cryotherapy, and that both lower pain levels than the control group [42].…”
Section: Discussionmentioning
confidence: 99%